Choledochodudenostomy for bile duct injuries: a less demanding option, in a demanding surgical situation - Aggarwal, Amulya; Mathur, Alok V.; Kaur, Manmeet (International Surgery Journal, 2019)
Cholecystectomy is one of the most common surgical procedure performed worldwide and therefore a common cause for iatrogenic biliary tract injury. Bile duct injuries are associated with significant morbidity and are a potentially fatal complication. Choledochodudenostomy in patients of post cholecystectomy bile duct injury can be done safely by experienced surgeons in CBD injuries distal to the confluence of the cystic and common hepatic duct after eradication of sepsis. Choledochoduodenostomy has its own technical advantages and it maintains the normal anatomy. As compared with a routine Roux-en-Y hepaticojejunostomy, CDD is technically easier, faster, requires less manipulation of the CBD, and is more physiological. We present a case report of a patient of laparoscopic cholecystectomy with CBD injury managed with choledochoduodenostomy who did extremely well after procedure with no immediate and delayed postoperative complication.